Conventional vs Islamic bonds announcements: the effects on shareholders' wealth - Mohd Ashhari, Zariyawati; Loo, Sin Chun; Md Nassir, Annuar (Canadian Center of Science and Education, 2009)
In this study the impact of Islamic bond and conventional bonds announcement on shareholder wealth was investigated. Data was employed from firms that listed in Bursa Malaysia for the period 2001 to 2006. A standard event study methodology with beta refinement using Blume’s method is employed to achieve the objective. The results indicate that there is a wealth effect by the announcement of Islamic bond issues. This is consistent with Mikkelson and Partch (1986) that states certain types of debts lead to abnormal return. The bond offering size appears to have a mild negative impact on the cumulative abnormal return.